Pengaruh Senam Bebek Berenang Terhadap Kemampuan Motorik Kasar Anak Usia 3-4 Tahun - Lestariningrum, Anik (Efektor, 2019)
This study aims to determine the effect of swimming duck gymnastics activity against gross motor skills of children aged 3-4 years using a type of pre-experiment research (non-design) with a one-shot case study design. The population of all of the students PAUD Labschool UN PGRI Kediri age 3-4 years with a sample of 10 children using saturated sampling technique. Data collection in this research is the method of observation and documentation conducted in the second semester of academic year 2016/2017 for a month that is January 2017. Test analysis used is the Wilcoxon Signed-Rank Test test because of the sample less than 30 and do not use control class and see the influence of the activities of duck gymnastics swimming in children before and after applied. The results of the Test Statistics showed the amount of Sig of 0.005 then the decision taken is to reject Ho because the Sig value is smaller than the alpha that has been set that is 0.05 so it shows there is a significant influence of the activity of swimming duck gymnastics in early childhood. From the results of Ranks also seen the mean value of 5.50. A positive mean value indicates that swimming duck gymnastics activities have a positive effect.